A Survey on Changes to the Canadian Anatomical Pathology Certification Examination Due to Coronavirus Disease 2019 and Implications for Competency-Based Medical Education. (13th December 2021) - Baranova, Katherina; Goebel, Emily A.; Wasserman, Jason; Osmond, Allison
The coronavirus disease 2019 pandemic resulted in a dramatic change in the Royal College of Physicians and Surgeons of Canada assessment process through elimination of the oral and practical components of the 2020 Anatomical Pathology examination. Our study sought to determine stakeholder opinions and experiences on these changes in the context of the 2019 implementation of competency-based medical education. Surveys were designed for residents and practicing pathologists. In total, 57 residents (estimated response rate 29%) and 185 pathologists (estimated response rate 19%) participated across Canada; 67% of pathologists disagreed with the 2020 Royal College examination changes, compared with 30% for residents (P = <.00001). When asked whether the Royal College examination should be eliminated, 95% of pathologists indicated they would be against this, compared to only 34% of residents (P = <.00001). Perceptions on changes to and importance of different components of assessment in competency-based medical education were similar between pathologists and residents, with participants perceiving assessment practices to have changed fairly little since its implementation, with the exception of more frequent feedback. Analysis of narrative comments identified several common themes around assessment, including the need for objectivity and standardization and the problem of failure-to-fail. However, residents identified numerous elements of their performance that can be assessed only through longitudinal evaluation. Pathologists, on the other hand, tended to view these aspects of performance as laden with bias. Our results will hopefully help guide future innovation in assessment by characterizing different stakeholder perspectives on key issues in medical education.